Sound insulation requirements in office buildings and schools - LANG, J. (Archives of Acoustics, 1985)
By order of the Austrian Ministry for Building and Technology the sound insulation between adjacent rooms in schools and office buildings has been measured. Additionally all teachers teaching in classrooms of schools and all employees working in office rooms were asked with a questionnaire to what extent they were satisfied by the acoustical conditions or disturbed by noise from the outside or from neighbouring rooms. From the correlation between the results of the sound insulation measurements and the subjective response, requirements for sound insulation in schools and office buildings have been established.